(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The purpose of thepresent study was to investigate the impact of type of faculty, sex andresidential status of the college students on Psychological Well-being. Thesample for the study comprised of 200 arts and 200 science college student fromferozepur city. The students in the sample were selected from various arts andScience College of ferozepur .city. Personal data sheet and Singh and Gupta(2001), Psychological Well-being scale were used to collect the required data.2x2x2 factorial design was planned. Where type of Stream, sex and residentialstatus were considered a independent variables and Psychological Well-being asdependent variables. Accordingly, 2x2x2 ANOVA was carried out to test thehypothesis. Results revealed no significant difference between the male andfemale students. There was higher level of Psychological Well-being among thestudents of science stream and students residing at their homes as compared tothe students of arts stream and students residing at hostels respectively.